A promising material for bone repair: PMMA bone cement modified by dopamine-coated strontium-doped calcium polyphosphate particles. Issue 10 (2nd October 2019) - Liu, Xing; Cheng, Can; Peng, Xu; Xiao, Hong; Guo, Chengrui; Wang, Xu; Li, Li; Yu, Xixun
Abstract : Polymethyl methacrylate (PMMA) bone cement has been widely used in clinics as bone repair materials for its excellent mechanical properties and good injection properties. However, it also has defects such as poor biological performance, high temperature, and the monomer has certain toxicity. Our study tried to modify the PMMA bone cement by doping with various particle weight fractions (5, 10 and 15%) of SCPP particles and polydopamine-coated SCPP particles (D/SCPP) to overcome its clinical application disadvantages. Our study showed that all results of physical properties of samples are in accordance with ISO 5833. The 15% D/SCPP/PMMA composite bone cement had much better biocompatibility compared with pure PMMA bone cement and SCPP/PMMA composite bone cement due to the best cell growth-promoting mineralization deposition on the surface of 15% D/SCPP/PMMA composite bone cements and Sr 2+ released from SCPP particles. Our research also revealed that the reaction temperature was found to be reduced with an increase in doped particles after incorporating the particles into composite bone cements. The novel PMMA bone cements modified by D/SCPP particles are promising materials for bone repair.